The Analysis of Private Timber Marketing in Bogor District - ‪Handian Purwawangsa; Maulida Oktaviarini; Faizal Mutaqin (Jurnal Silvikultur Tropika, 2021)
The private forest is one of alternatives that played an important role in fulfillment of a need raw materials management industry wood and the needs of wood. Development of private forest can improve the people and land revenue increase productivity. Research conducted in sub-district Leuwisadeng, Cigudeg, and Jasinga shows that there are some marketing actors involved in marketing wood of the private forest of them are farmers, traders, and sawmill industries. The marketing of the three actors formed four marketing channels are grouped based marketing actors and average skidding distance. Channels that most efficient among fourth the channels is a channels II with the percentage of farmer’s share as 46.93 % and the ratio of K/B by 5.45. Types of plants most favored by farmers and consumers is the type of sengon it because sengon having a short, the age of harvest readily grows, and easy cultivation. The consumer likes kind of plant is because sengon have reachable prices, sengon not easily bad condition wood and widely available in market. Key words: bogor, farmer’s share, marketing efficiency rasio, private forest